Extreme Learning Machine in Laser-Assisted Machining Using Waste Palm Cooking Oil - Yasmin, Farhana; Tamrin, K. F.; Sheikh, N. A. (Apple Academic Press, 2020)
Use of lubricating/cutting fluids is crucial in machining processes to reduce friction, alleviate heat accumulation and prolong tool life. To minimize environmental and health impacts, a number of studies using vegetable oil-based cutting fluid have been investigated and reported demonstrating similar performance obtained using commercial cutting fluids. However, massive use of vegetable oil for such purposes would undeniably trigger issues of food security. In order to mitigate food waste, the primary objective of the chapter is to demonstrate the application of waste palm cooking oil as a potential lubricating fluid in laser-assisted machining of metal. By considering kinematic and dynamic viscosities of the waste cooking oil, its effects on surface roughness and tool wear are studied by predicting using extreme learning machine (ELM). The prediction results show that the average errors are only 0.51% and 1.19% for surface roughness and flank wear, respectively, suggesting good agreement between observation and prediction.